KNOWLEDGE, ATTITUDE AND PRACTICES ABOUT HOSPITAL WASTE MANAGEMENT AMONG RURAL AND URBAN HEALTH CARE WORKERS (The Research of Medical Science Review, 2025)
Background: Hospital waste management functions as an essential healthcare component because improper waste control leads to substantial health dangers for both public health and environmental systems. Poor biomedical waste segregation practices coupled with improper handling and disposal create infrastructure damage and propagate infections while reducing available resources. The research investigates how knowledge, attitudes and practices (KAP) in waste management differ between healthcare workers employed in both urban and rural locations of Lahore Pakistan seeking to identify vital recommendations areas. Objective: This research study investigates the comprehension levels together with conduct and opinions of healthcare personnel who work in hospital waste supervision systems. Methodology: Healthcare workers from two urban and two rural hospitals in Lahore participated in this comparative cohort study. The research involved a total of 100 healthcare experts who split evenly into urban and rural hospitals as identified through a random sampling technique. Healthcare workers provided their responses through a structured questionnaire that gathered both demographic information and assessment of their knowledge and attitudes and practical waste management actions. Hospital personnel completed a survey consisting of multiple-choice questions alongside Likert-scale responses which focused on waste segregation practices and waste handling along with waste disposal procedures. Data was analyzed through descriptive statistics together with chi-square tests to identify KAP score differences between urban and rural participants. Results: Results showed urban healthcare workers exhibited superior understanding and positive perceptions about waste management than rural participants since urban employees recognized 71.1% of waste categories yet rural workers identified only 55%. The evaluation of knowledge demonstrated a substantial difference between rural workers (scored 58%) and their urban counterparts (scored 72%) whereas urban workers earned higher total attitude scores (4.2) than rural workers (3.6). Resource constraints were identified more often by rural healthcare workers than urban colleagues (72% compared to 45%) and training fell short for 50% of rural staff and waste segregation adherence stood limited at 37% among rural workers. A statistically significant difference (p < 0.05) arose in training acquisition, sanitation practices, and policy understanding between urban workers and those from rural areas. Conclusions: The data makes it clear that hospital waste management requires specific intervention strategies to better address waste management issues in rural medical facilities. Waste management efforts require better resources while enhanced training sessions and stronger compliance with waste management rules to bridge regional disparities. These implemented measures will decrease health risks and environmental threats and raise total adherence to healthcare waste management requirements. Implications: Equal and lasting waste management practices in healthcare settings need systematic remediation of rural institution barriers to function effectively. Healthcare facilities can achieve higher compliance levels as well as better public health results by closing training and resource and awareness deficiencies but maintaining international waste management protocols.